Amustaline (S‐303) treatment inactivates high levels of Zika virus in red blood cell components. Issue 3 (5th February 2017) - Laughhunn, Andrew; Santa Maria, Felicia; Broult, Julien; Lanteri, Marion C.; Stassinopoulos, Adonis; Musso, Didier; Aubry, Maite
Abstract : BACKGROUND: The potential for Zika virus (ZIKV) transfusion‐transmission (TT) has been demonstrated in French Polynesia and Brazil. Pathogen inactivation (PI) of blood products is a proactive strategy to inactivate TT pathogens including arboviruses. Inactivation of West Nile, dengue, Zika, and chikungunya viruses was previously demonstrated by photochemical treatment with amotosalen and ultraviolet A (UVA) illumination. In this study, we evaluated ZIKV inactivation in red blood cell (RBC) components by a chemical approach that uses amustaline (S‐303) and glutathione (GSH). STUDY DESIGN AND METHODS: RBC components were spiked with a high titer of ZIKV. Viral titers (infectivity) and ZIKV RNA loads (reverse transcription–polymerase chain reaction) were measured in spiked RBCs before and after S‐303 and GSH treatment and confirmed using repetitive passages in cell culture. A mock‐treated arm validated the approach by demonstrating stability of the virus (infectivity and RNA load) during the process. RESULTS: The mean ZIKV infectivity titer and RNA load in RBCs were 5.99 ± 0.2 log 50% tissue culture infectious dose (TCID50 )/mL and 7.75 ± 0.16 log genomic equivalents/mL before inactivation. No infectivity was detected immediately after S‐303 and GSH treatment and after five serial passages in cell culture. CONCLUSION: Complete ZIKV inactivation of more than 5.99 log TCID50 /mL in RBCs was achieved using S‐303 and GSH at levels higher than those found in asymptomatic ZIKV‐infected blood donors. Therefore, the S‐303 and GSH PI system is promising for mitigating the risk of ZIKV TT.